Between‐day reliability of the trapezius muscle H‐reflex and M‐wave. Issue 6 (7th September 2015) - Vangsgaard, Steffen; Hansen, Ernst a.; Madeleine, Pascal
ABSTRACT: Introduction : The aim of this study was to investigate the between‐day reliability of the trapezius muscle H‐reflex and M‐wave. Methods : Sixteen healthy subjects were studied on 2 consecutive days. Trapezius muscle H‐reflexes were evoked by electrical stimulation of the C3/4 cervical nerves; M‐waves were evoked by electrical stimulation of the accessory nerve. Relative reliability was estimated by intraclass correlation coefficients (ICC2, 1 ). Absolute reliability was estimated by computing the standard error of measurement (SEM) and the smallest real difference (SRD). Bland–Altman plots were constructed to detect any systematic bias. Results : Variables showed substantial to excellent relative reliability (ICC = 0.70–0.99). The relative SEM ranged from 1.4% to 34.8%; relative SRD ranged from 3.8% to 96.5%. No systematic bias was present in the data. Conclusions : The amplitude and latency of the trapezius muscle H‐reflex and M‐wave in healthy young subjects can be measured reliably across days. Muscle Nerve 52 : 1066–1071, 2015